Calendar of teaching aids in the al-Azhari Arabic Curriculum For the Higher Religious Secondary in the Malaysian state of Johor - Shatnawi, Islam; Bin Abdul Ghani , kamarulzaman; Che Noh, Mohd (Jordan Journal of Educational Sciences, 2014)
This study aimed to identify the educational methods and evaluation in al-Azhari Arabic curriculum at higher religious schools in the Malaysian state of Johor . The researchers used the descriptive analytical method and the tool questionnaire, where questionnaires were distributed to teachers, has sample consisted of 52 teachers of the curriculum, as well as the identification of a second have been distributed to a sample of students , consisting of 242 high school students of religious high in the state of the core , which was selected in the manner stratified random relative , and conducted validity and reliability of the instrument. Following the appropriate statistical methods of occurrences and percentages and standard deviations , the study found the results of several of them ; lack of use of teaching aids , and lack of awareness of its importance , and the lack of availability of seats allocated for use , and the lack of availability of teaching aids in schools , and the lack of suitable , some often in the al-Azhari Arabic language curriculum; The study recommended the need to provide modern library with books and references Simplified Arabic , and provide schools with the means of education and modern technologies and the training of teachers